Synthesis And Properties Of Phenolic Based Hybrid Carbon Nanotube Inorganic Filled Composites - Saleh, Siti Shuhadah Md (2017)
The use of a single filler in polymer composites does not always meet the on-demand requirements of an advanced polymer composite application. Therefore, producing a hybrid filler that contains more than one filler is necessary. Recently carbon nanotubes (CNTs) were hybridized with others fillers to achieve the combined effects of the filler. The combinations of the filler (hybrid filler) should have a strong physical and chemical interaction with each other in order to achieve the optimum reinforcing effect. This study proposed the chemical vapour deposition (CVD) method to produce a CNTs hybrid with inorganic fillers and this synthesised CNTs hybrid, was used as filler in phenolic composites. The first part of the research was the investigation of the CNTs/alumina hybrid and its processing parameter such as calcinations temperatures and duration. The comparative study of hybrid CNTs using the CVD method and the physical method (conventional) on the properties of the phenolic composite were also studied. The phenolic composites were fabricated via hot mounting process. The tribological properties were investigated using a pin-on-disk tester under different sliding conditions. The results showed that 10 hours duration of calcination and 900oC were the best parameters to growth the CNTs hybrid. The result also revealed that hybridising the CNTs via CVD improves the hardness, thermal conductivity and tribological properties of the phenolic hybrid composite. In the second part of the research, empirical models with different independent variables for the tribological behaviour of CNTs/alumina filled phenolic composites were developed using the response surface methodology (RSM) approach. The optimisation of the response as a function of the independent variable was generated. It shows that 5HYB/PHENOLIC exhibited better wear performance than 5PHY/PHENOLIC composites.In the third part, the suitability of calcium carbonate, talc and dolomite to growth the CNTs in the production of CNTs/inorganic hybrid compounds using the CVD method was investigated. The results showed that the CNTs growth on the calcium carbonate, talc and dolomite particles, which means they are also suitable as a support material in CNTs hybrids (growth using a nickel metal catalyst and methane as the carbon feedstock at 800oC). The result also revealed that the CNTs/inorganic hybrid improved the hardness and thermal properties of the phenolic composites